A field study on correlations between macroscopic gut health scoring, histological measurements and performance parameters in broilers. Issue 6 (2nd November 2021) - Ringenier, M.; Caekebeke, N.; De Meyer, F.; Van Limbergen, T.; Eeckhaut, V.; Ducatelle, R.; Van Immerseel, F.; Dewulf, J.
ABSTRACT: Optimal intestinal health is a prerequisite for sustainable poultry production. Intestinal health can be evaluated by scoring macroscopic intestinal abnormalities and by histological measurements. The aim of this study was to evaluate correlations between macroscopic gut appearance scoring (GAS), coccidiosis lesion scoring, histological measurements and performance parameters in broilers under field conditions. Therefore, a cross-sectional study was performed on 50 broiler farms where birds were sampled at 28 days of age. The GAS was determined by scoring the absence or presence of 10 macroscopically visible parameters of the gastrointestinal tract, yielding a GAS between 0 and 10, with 0 meaning no gut abnormalities. On individual bird level, when birds had a GAS score of 6 or higher, significantly shorter villi were found in the duodenum. Also, CD3+ T-lymphocyte area percentage in the duodenal mucosa was significantly negatively correlated to villus length. On farm level, the average feed conversion ratio (FCR) was 1.59 ± 0.04 [1.52–1.73]. However, no correlations were found between the GAS at the age of 28 days and the prevalence of coccidiosis, nor did coccidiosis lesion scoring correlate with the FCR. Also, a higher GAS could not be associated with a higher FCR. In conclusion, on all farms a certain degree of macroscopic visible gut and coccidiosis lesions were present in birds of 28 days of age, while this did not correlate with the FCR. This suggests that broilers are able to cope with a certain level of gut damage before it influences the overall performance.